Method validation for determination of manganese, zinc, nickel, chromium,molybdenum, cadmium and lead released from aluminium cooking utensils - Waluvanaruk, jitwilai; Luesaiwong, Wandee (Bulletin of Applied Sciences, 2023)
Aluminium cooking utensils are widely used in Thailand and other ASEAN countries due to their lightweight, transferring heat quickly and cheap prices. There is a trade-off, however, because almost all aluminium cooking utensils can release metals through food when they contact with acidic foodstuffs. The method for determination of manganese, zinc, nickel, chromium, molybdenum, cadmium and lead released from aluminium cooking utensils by inductively coupled plasma optical emission spectrometry (ICP-OES) was validated according to Metals and alloys used in food contact materials and article. A practical guide for manufactures and regulators [1].Results showed that instrument working ranges of manganese, nickel, chromium, molybdenum, cadmium and lead were 0.05 - 1.0 mg/L and zinc was 0.10 - 1.0 mg/L. The limit of detections of manganese, zinc, nickel, chromium, molybdenum, cadmium and lead were 1.0, 7.4, 0.6, 0.3, 0.3, 0.2 and 2.1 µg/L. The limit of quantitations of zinc was 0.10 mg/L and the others were 0.05 mg/L. The bias and precision studies showed that percentage of recovery and relative standard deviations of seven elements were 83.8 - 98.4 and 1.17 - 4.17, respectively. While the expanded uncertainties of all elements were less than ± 15 %, at the confidence level of 95%. Therefore, this test method for determination of seven released elements from aluminium cooking utensils by ICP-OES is valid and fits for intended use.